The Impact of Online Learning Service Quality on Student Satisfaction During the COVID-19 Pandemic - Olufemi A. Oroye (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Online learning, also known as e-learning, has played a crucial role in enabling remote education, benefiting many institutions during the COVID-19 pandemic. However, student satisfaction is essential for effectively implementing and utilizing online learning platforms, particularly for institutions that have adopted or plan to adopt them. This study examines the quality of online learning services at Bells University of Technology during the COVID-19 lockdown and its impact on student satisfaction. Data were collected and analyzed using descriptive analysis and Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses. The findings indicate that the quality of online learning services significantly influences student satisfaction—higher service quality leads to greater student satisfaction. Keywords: Online Learning Service Quality, Student Satisfaction, Covid-19, Partial Least Squares Structural Equation Modeling (PLS-SEM). .